Arahan Pengelolaan Berdasarkan Tipologi dan Pemanfaatan Pemakaman di Kelurahan Karang Joang: Management Directions Based on Typology and Use of Cemeteries in Karang Joang Village - Tri Prabowo, Endra; Kadri, Mohtana Kharisma; Mustofa, Umar; Pratama, Maryo Inri (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2023)
Initially, cemeteries only had the function of burying bodies, but as time went by, cemeteries had other functions, for example ecological, water absorption, socio-cultural, aesthetic and disaster management functions. However, cemeteries in Balikpapan City generally only function to bury bodies so that the function of green open spaces in cemeteries is less than optimal. The aim to be achieved in this research is to formulate burial management directions based on typology and its utilization function so that the function of the cemetery green space is more optimal. Comparative descriptive analysis is a method used in formulating burial management directions based on typology and its use by comparing with best practices and guidelines so that the output that has been obtained is that ecological functions must provide a typology such as animal-inviting rain gardens, water catchment functions must provide a typology such as ponds. retention, the aesthetic function must increase the visual aesthetics of pedestrian paths and plazas/squares, the socio-cultural function must provide gazebos, prayer rooms and chairs for interaction and the disaster management function must provide a gathering point.